Effectiveness of N95 respirators versus surgical masks against influenza: A systematic review and meta-analysis - Long, Youlin; Hu, Tengyue; Liu, Liqin; Chen, Rui; Guo, Qiong; Yang, Liu; Cheng, Yifan; Huang, Jin; Du, Liang (Journal of evidence-based medicine, 2020)
Previous meta-analyses concluded that there was insufficient evidence to determine the effect of N95 respirators. We aimed to assess the effectiveness of N95 respirators versus surgical masks for prevention of influenza by collecting randomized controlled trials (RCTs). We searched PubMed, EMbase and The Cochrane Library from the inception to January 27, 2020 to identify relevant systematic reviews. The RCTs included in systematic reviews were identified. Then we searched the latest published RCTs from the above three databases and searched ClinicalTrials.gov for unpublished RCTs. Two reviewers independently extracted the data and assessed risk of bias. Meta-analyses were conducted to calculate pooled estimates by using RevMan 5.3 software. A total of six RCTs involving 9 171 participants were included. There were no statistically significant differences in preventing laboratory-confirmed influenza (RR = 1.09, 95% CI 0.92-1.28, P > .05), laboratory-confirmed respiratory viral infections (RR = 0.89, 95% CI 0.70-1.11), laboratory-confirmed respiratory infection (RR = 0.74, 95% CI 0.42-1.29) and influenzalike illness (RR = 0.61, 95% CI 0.33-1.14) using N95 respirators and surgical masks. Meta-analysis indicated a protective effect of N95 respirators against laboratory-confirmed bacterial colonization (RR = 0.58, 95% CI 0.43-0.78). The use of N95 respirators compared with surgical masks is not associated with a lower risk of laboratory-confirmed influenza. It suggests that N95 respirators should not be recommended for general public and nonhigh-risk medical staff those are not in close contact with influenza patients or suspected patients.